Lathrolestes buccinator Holmgren 1857 ... - Reshchikov, Alexey (Zenodo, 2012)
Lathrolestes buccinator (Holmgren, 1857) Material: specimens, female, 2males, Russia, Kamchatka, Kozyrevsk, deciduous., motley grass, 24.vii.1985, D. Kasparyan; female, Russia, Buryatia, 01.vii.1971, D. Kasparyan; 2females, Russia, Khabarovsky Kray, Khekhtsyr, Levaya river, coniferous-deciduous forest, 02.vii.1983, D. Kasparyan; male, Russia, Sakhalin, Aniva, 04.vii.1973, D. Kasparyan; male, Russia, Khabarovsky Kray, Vysokogorny, birch wood with Larix, 10.vii.1983, D. Kasparyan; female, Russia, Primorsky Kray, Anisimovka, 26–27.vi.1996, S. Belokobylskij. Distribution: Palearctic. ... : Published as part of Reshchikov, Alexey, 2012, Review and key to Russian Far East Lathrolestes (Hymenoptera, Ichneumonidae), pp. 1-32 in Zootaxa 3414 on page 25, DOI: 10.5281/zenodo.281927 ...